Plantationocene systems and communal disruptions in N.K. Jemisin’s broken earth trilogy : an ecogothic perspective - Anita Harris Satkunananthan (Penerbit Universiti Kebangsaan Malaysia, 2022)
N.K. Jemisin’s critically acclaimed Broken Earth trilogy examines life in a post-apocalyptic alternate universe after a planet is cracked, bleeding and about to die. The trilogy does not seek to redeem the earth or a fractured environment. Rather, the novels demonstrate the ways in which characters develop, dissolve and mutually destroy or support each other. Jemisin’s conception of nature is unique and almost antithetical to human survival, but the roots of this destruction go deep. The fractured economies and governments within this post-apocalyptic universe paint a haunting picture of a world whose geopolitics are affected by the nature it has despoiled and disintegrated. The trilogy is a fitting fable for a planet in which climate change has affected endangered species, ecosystems and world economics. I apply a postcolonial ecoGothic lens to the analysis of the Broken Earth trilogy. This postcolonial ecoGothic approach will be married to a consideration of Jason C Moore’s unveiling of the Capitolocene through the lens of Donna Haraway’s and Anna Tsing’s positioning of a Plantationocene to look at patterns of power and domination. This paper is particularly concerned with the ways in which these patterns are related to the condition of societies living under siege and the ways in which these societies mimic patterns of colonial domination. The proposed outcome of this analysis will be to strip the layers of the Broken Earth trilogy to unearth what the narrative reveals about the environmental travails and geopolitical dissolutions that haunt our existences in what has been dubbed the Anthropocene.